Repositioning Role of Financial Bank Institutions and Non-Bank in Efforts to Empowerment Populist of Economic Autonomy and Development Area Based on Good Governance - Amnatia R. Abdullah (Journal of Economic, Business, and Administration (JEBA), 2021)
Poverty in some developing countries is still a problem that is so complex and multidimensional, and highly impact on the quality of human life, especially in Indonesia are still many people living under the poverty line, thus demanding the central government and local governments to continue to coordinate and make langah-step accelerate growth in strategic development towards self-reliance, so that each region can prepare all the potential, capabilities and infrastructure areas to achieve the success of regional autonomy with the local government system based on good governance. The purpose of this study was to determine and analyze the role of Financial Institutions Banks and Non-Bank In Effort Populist Economic Empowerment and Development of Regional Autonomy Based On Good Governnance. This research uses descriptive qualitative approach. The collecting data is to use the method of theoretical research Library research is sourced from literature and books related to the research. Furthermore, the method used field research that is interalia, by direct observation to the object of research and conduct interviews. Based on the results of the study indicate that there is still a lot of business people who have difficulties in obtaining venture capital even to survive in this era of business competition. Most of these micro businesses rely more on the strength of their own capital and the capital of the other party who is not a bank or non-bank institutions.